2008
DOI: 10.1038/ngeo127
|View full text |Cite
|
Sign up to set email alerts
|

Significant contribution of the 18.6 year tidal cycle to regional coastal changes

Abstract: International audienceAlthough rising global sea levels will affect the shape of coastlines over the coming decades(1,2), the most severe and catastrophic shoreline changes occur as a consequence of local and regional-scale processes. Changes in sediment supply(3) and deltaic subsidence(4,5), both natural or anthropogenic, and the occurrences of tropical cyclones(4,5) and tsunamis(6) have been shown to be the leading controls on coastal erosion. Here, we use satellite images of South American mangrove-colonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 25 publications
3
90
0
1
Order By: Relevance
“…These tidal currents can move beach sand and are particularly important between islands and at river mouths where flow velocities are high (Cambers 1998). In addition to the tidal cycles that occur over the short-term, a study by Gratiot et al (2008) has demonstrated that the 18.6 year nodal tidal cycle contributes significantly to regional coastal changes. Currents are important because of their role in transporting sediment, and to a smaller extent, erosion.…”
Section: Introductionmentioning
confidence: 99%
“…These tidal currents can move beach sand and are particularly important between islands and at river mouths where flow velocities are high (Cambers 1998). In addition to the tidal cycles that occur over the short-term, a study by Gratiot et al (2008) has demonstrated that the 18.6 year nodal tidal cycle contributes significantly to regional coastal changes. Currents are important because of their role in transporting sediment, and to a smaller extent, erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Following these criteria, it can be seen that only events since 2012 are taken from the tide gauge record. A notably stormy winter in 2013/2014 coincided with the peak of the 18.6 year tidal lunar cycle (Gratiot et al 2008;Haigh et al 2016).…”
Section: Surge Characteristicsmentioning
confidence: 99%
“…Coastal waters in French Guiana are extremely turbid, with visibility measured in centimeters rather than meters. Sediments from the Amazon are transported northwest to French Guiana by the Guiana Current (Muller-Karger et al 1988, Gratiot et al 2008, so coastal marine organisms here likely encounter prey primarily by smell, hearing and lateral line sense, rather than by sight (Janssen et al 1995, Montgomery et al 1995, Hartman & Abrahams 2000. Utne-Palm (2002) demonstrated that turbidity affects foraging behaviour by increasing the search time and decreasing the reactive distance, thus reducing the catchability of prey for piscivorous fishes.…”
Section: The Diet Of Goliath Groupers In Frenchmentioning
confidence: 99%
“…The marine environment off French Guiana is under the influence of the Amazon River; sediments are transported to the north of the Amazon and all along the Guiana shelf by the North Brazil Current (Gratiot et al 2008), making local marine waters extremely turbid and leading to low salinity. Although there is an abundance of marine organisms in this area, the ecology of these organisms, including goliath grouper, is poorly known.…”
Section: Goliath Grouper Epinephelus Itajaramentioning
confidence: 99%